BUNGA MENDOWE: CERITA RAKYAT NASSENREMPULU DAN PENGARUHNYA DALAM KEHIDUPAN - Mustafa, Mustafa (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2017)
Bunga Mendowe is one of the literary works of the Massenrempulu community that is loaded with values and concepts of life delivered orally from generation to generation. This paper describes one type of local legend literary works. The story tells about life in the community especially the issue of marriage that is not based on love and the consequences of leaving the wife for so long time. This story is so much more interesting to be flavored with supernatural so that it is interesting to read and digest. In addition, the story can be a material advice and learning for children and grandchildren to avoid misguidance. The theory used is Levi-Strauss-based theory which is exemplified by Ahimsa in the book Structuralism of Levi-Strauss Myth and Literary Works on Pitoto 'si Muhammad'. The result found indicates a structured relationship between elements in the story and social conditions in society. Keywords: Folklore, Story structure, Social relationship